What Happened to the 'Development' in Sustainable Development? Business Guidelines Two Decades After Brundtland. (27th April 2011) - Barkemeyer, Ralf; Holt, Diane; Preuss, Lutz; Tsang, Stephen
ABSTRACT Over 20 years ago Our Common Future presented a conceptualization and explanation of the concept of sustainable development. Since then, numerous alternative definitions of the concept have been offered, of which at least some are exclusive to each other. At the same time, the role of business in the transition to sustainable development has increasingly received attention. Bringing these two trends in sustainable development together, this paper returns to the Brundtland version of the concept to examine to what extent the original principles of sustainable development are still embedded within key business guidelines, namely the UN Global Compact, the OECD Guidelines for Multinational Enterprises, the ICC Business Charter for Sustainable Development, the CAUX Principles, the Global Sullivan Principles and the CERES Principles. The findings suggest that these business guidelines tend to emphasize environmental rather than social aspects of sustainable development, in particular to the detriment of the original Brundtland prioritization of the needs of the poorest. Furthermore, the attention to environmental aspects stresses win–win situations and has a clear managerialist focus; whereas more conceptual environmental issues concerning systems interdependencies, critical thresholds or systemic limits to growth find little attention. The normative codes and principles targeted at the private sector therefore not only add another voice to the multiple discourses on sustainable development but also contribute to a reinterpretation of the original agenda set by Brundtland towards conceptualizations of sustainable development around the needs of industrialized rather than developing countries. Copyright © 2011 John Wiley & Sons, Ltd and ERP Environment.